Implementation of Deregistration and Export Back Aircraft Based on Cape Town Convention in Indonesia - Rifaa Eka Novisna; Riyanto, Sigit (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2024)
The Cape Town Convention is a regulation that creates international standards for security interests (liens), leases, and various legal remedies for default in financing agreements, including repossession. Nevertheless, several incidents resulted in losses to the lessor because the Cape Town Convention was not implemented properly in Indonesia. This research aimed to analyze Indonesians’ compliance with implementing the deregistration and re-export of aircraft based on the Cape Town Convention. Apart from that, this research also examined the obstacles faced by the Indonesians when implementing the Cape Town Convention, especially in implementing Deregistration and Export (IDERA) in Indonesia, and whether they have solutions to overcome these obstacles. This research used a Normative-Empirical research methodology that analyzes the implementation of written legal provisions and whether the provisions of the statutory regulations have been implemented properly. This research employed qualitative methods to analyze the data collected. The conclusion is first, the Indonesian Government is implementing the deregistration and export of aircraft adequately based on the results of analysis by comparing the regulations and interviews with practitioners; second, the Indonesian Government in the process of implementing the Deregistration and Export Back of aircraft faces several obstacles, including the lack of legal certainty regarding the implementation mechanism and limited authority; and third, the Indonesian Government has a solution to overcome obstacles, including revising related regulations and becoming a mediator if there are problems as a form of legal filling. Therefore, it can provide certainty and peace of mind for lessors when receiving collateral in the form of aircraft in Indonesia. The results of this research are expected to increase understanding regarding deregistration and export back of aircraft based on the Cape Town Convention in Indonesia so that many parties understand and comprehend this matter.